Formulation and Evaluation of Microemulsion Based Topical Hydrogel Containing Lornoxicam - Biswajit Biswal, Nabin Karna, Jyotiranjan Nayak, Vivek Joshi (Journal of Applied Pharmaceutical Science, 2014)
The objective of present study was to formulate hydrogel thickened Lornoxicam transdermal formulation. Eutectic mixture of camphor and menthol was chosen as oily phase (maximum 10%), solvent for Lornoxicam and powerful penetration enhancer. Tween 80, ethanol and Carbopol 934p, HPMC K-15M and Xanthan gum were selected as surfactant, co-surfactant and hydrogel thickening agent respectively. Ternary phase diagrams were constructed to obtain the concentration range of oil phase, surfactant and co-surfactant for microemulsion formulation. Hydrogel thickened microemulsions were characterized for pH, viscosity, spreadability, in vitro drug transport study with excised rat skins and invivo anti inflammatory activity. The average drug transport rate of optimized hydrogel thickened microemulsion containing 1 % w/w Lornoxicam, 10 % w/w oily phase of camphor and menthol, 30 % w/w tween 80, ethanol (2:1), 57 % w/w water, 1.5 % w/w Carbopol 934p and 0.5 % w/w Triethanolamine through rat skin was 2.02 μg/cm2/h . The percentage in vitro drug release of optimized hydrogel thickened microemulsion was 78.91 %. pH, viscosity and spreadability of optimizes batch was 6.4, 5291 cps and 5.98 gcm/sec.
Keywords: Lornoxicam, Eutectic mixture, Ternary phase, Microemulsion, Hydrogel.